Policing unruly women: The state and sexual violence during the Northern Irish Troubles. (May 2017) - O'Keefe, Theresa
Abstract: Northern Ireland is not typically cited as an example of a conflict reliant on sexual violence. This is due, in part, to how wartime sexual violence is conceptualised, measured and normalised. Adopting a continuum of sexual violence model to view a range of abusive behaviours as interconnected the paper argues that a clear pattern of state-perpetrated sexual violence is discernible during the Troubles. Based on feminist ethnographic research it details how the state through prison authorities, police, soldiers and other security forces weaponised sexual violence as a means of disciplining and punishing republican women deemed deviant for transgressing gender norms. Two key interfaces where republican women regularly interacted with security forces during the war - everyday policing and detention - illustrate both the importance of viewing the a range of sexually abusive practices on a continuum and how such practices were weaponised for the purposes of policing unruly, disruptive, transgressive women. Highlights: State-perpetrated sexual violence was a prominent feature of the Northern Irish Troubles. Imprisoned Irish republican women repeatedly suffered state-perpetrated sexual violence in the form of strip searches. State-perpetrated sexually abusive threats and slurs represent the same structural violence as strip searches. A continuum of wartime sexual violence model illuminates how webs of state power work to control and punish transgressive women.